Reproductive aspects of Jack mackerel Trachurus murphy - Perea, Ángel (2013)
The time series of monthly gonadosomatic index (GSI) and biannual size at first maturity of Jack mackerel Trachurus murphyiNichols 1920 in Peru between 1967 and 2012 is analyzed and discussed. The annual and interannual variation of the reproductive cycle was determined. It is shown that in Peru T. murphyihas a single relatively extended spawning period with a maximum in November each year. It is also shown that for more than four decades T. murphyi has spawned regularly every year in Peruvian waters. The reproductive activity of T. murphyi has a greater variability off Peru and the spawning period has peaks of lesser magnitude but extend longer than observed in the spawning occurring off Chile. The analyses of the sizes at first maturity of Jack mackerel in Peruvian waters did not show significant changes throughout the entire period observed.